The aminoglycoside resistance-promoting AmgRS envelope stress-responsive two-component system in Pseudomonas aeruginosa is zinc-activated and protects cells from zinc-promoted membrane damage. Issue 5 (5th March 2019) - Poole, Keith; Hay, Thomas; Gilmour, Christie; Fruci, Michael
Abstract : Exposure of wild-type (WT) Pseudomonas aeruginosa PAO1 to ZnCl2 (Zn) yielded a concentration-dependent increase in depolarization of the cytoplasmic membrane (CM), an indication that this metal is membrane-damaging. Consistent with this, Zn activated the AmgRS envelope stress-responsive two-component system (TCS) that was previously shown to be activated by and to protect P. aeruginosa from the membrane-damaging effects of aminoglycoside (AG) antibiotics. A mutant lacking amgR showed enhanced Zn-promoted CM perturbation and was Zn-sensitive, an indication that the TCS protected cells from the CM-damaging effects of this metal. In agreement with this, a mutant carrying an AmgRS-activating amgS mutation was less susceptible to Zn-promoted CM perturbation and more tolerant of elevated levels of Zn than WT. AG activation of AmgRS is known to drive expression of the AG resistance-promoting mexXY multidrug efflux operon, and while Zn similarly induced mexXY expression this was independent of AmgRS and reliant on a second TCS implicated in mexXY regulation, ParRS. MexXY did not, however, contribute to Zn resistance or protection from Zn-promoted CM damage. Despite its activation of AmgRS and induction of mexXY, Zn had a minimal impact on the AG resistance of WT P. aeruginosa although, given that Zn-tolerant AmgRS-activated amgS mutant strains are AG resistant, there is still the prospect of this metal promoting AG resistance development in this organism.